Decomposition and nutrient release by green manures in a tropical hillside agroecosystem - Cobo Borrero, Juan G.; Barrios, E.; Kass, DCL; Thomas, Richard J. (Springer, 2002)
The decomposition and nutrient release of 12 plant materials were assessed in a 20-week litterbag field study in hillsides from Cauca, Colombia. Leaves of Tithonia diversifolia (TTH) and Indigofera constricta (IND) decomposed quickly (k=0.035±0.002 d?1), while those of Cratylia argentea (CRA) and the stems evaluated decomposed slowly (k=0.007±0.002 d?1). Potassium presented the highest release rates (k>0.085 d?1). Rates of N and P release were high for all leaf materials evaluated (k>0.028 d?1) with the exception of CRA (N and P), TTH and IND (P). While Mg release rates ranged from 0.013 to 0.122 d?1, Ca release was generally slower (k=0.008–0.041 d?1). Initial quality parameters that best correlated with decomposition (P>0.001) were neutral detergent fibre, NDF (r=?0.96) and in vitro dry matter digestibility, IVDMD (r=0.87). It is argued that NDF or IVDMD could be useful lab-based tests during screening of plant materials as green manures. Significant correlations (P>0.05) were also found for initial quality parameters and nutrient release, being most important the lignin/N ratio (r=?0.71) and (lignin+polyphenol)/N ratios (r=?0.70) for N release, the C/N (r=0.70) and N/P ratios (r=?0.66) for P release, the hemicellulose content (r=?0.75) for K release, the Ca content (r=0.82) for Ca release, and the C/P ratio (r=0.65) for Mg release. After 20 weeks, the leaves of Mucuna deerengianum released the highest amounts of N and P (144.5 and 11.4 kg ha?1, respectively), while TTH released the highest amounts of K, Ca and Mg (129.3, 112.6 and 25.9 kg ha?1, respectively). These results show the potential of some plant materials studied as sources of nutrients in tropical hillside agroecosystems.